Long bone structural proportions and locomotor behavior in Cercopithecidae. Issue 132 (July 2019) - Ruff, Christopher B.; Harper, Christine M.; Goldstein, Deanna M.; Daegling, David J.; McGraw, W. Scott
Abstract: Limb bone articular and diaphyseal proportions have been shown to relate to locomotor behavior in broad comparisons across catarrhines, but comparisons among phylogenetically and functionally more closely related species may be particularly useful in investigating form-function relationships that can be applied to fossil taxa. Here we compare inter- and intra-limb proportions of diaphyseal strength and articular surface area and breadth of the femur and humerus with frequencies of leaping and vertical climbing behavior in 13 cercopithecid species. Leaping frequency is highly positively correlated with femoral/humeral diaphyseal strength, moderately positively correlated with femoral/humeral articular breadth, and less highly correlated with femoral/humeral articular surface area. These results are consistent with predicted higher bending loads as well as joint reaction forces on the femora of leapers. Surface areas may show a weaker association because they also directly impact joint excursion and are thus more influenced by other aspects of locomotion, including climbing. Climbing frequency is positively correlated with humeral head articular surface area/diaphyseal strength, but weakly negatively correlated with femoral head articular surface area/diaphyseal strength. These combined trends lead to a strong negative association between climbing and femoral/humeral head surface area. Femoral/humeral diaphyseal strength and distal articular breadth are not correlated with climbing frequency. The climbing results are consistent with greater shoulder mobility in more frequent vertical climbers. The lack of such a relationship in the femur among these taxa contrasts with earlier findings for catarrhines more generally, including hominoids, and may be a result of different climbing kinematics in cercopithecoids involving less hip abduction than in hominoids. Different use of the forelimb during climbing in cercopithecoids and hominoids may also explain the lack of association between femoral/humeral diaphyseal strength and climbing in the present study, in contrast to comparisons across catarrhines more generally.